Internationalization experiences as catalysts for the development of socio-emotional and intercultural (SEI) competences in engineering students - Willer Ferney Montes Granada; Sara María Yepes Zuluaga; Andres Herrera Granda (Cogent Education)
Internationalization in Higher Education arises as a transformative response to globalization, aimed at improving education quality and fostering the development of key competencies. This study evaluates the impact of internationalization experiences offered at a Colombian university on the development of socio-emotional and intercultural competencies (SEI) among engineering students. A quantitative post-test quasi-experimental design was employed, with data collected from 274 students using the ICSEI self-perception instrument; Inferential quantitative techniques such as Pearson correlation and t-student were used. The results indicate a statistically significant improvement in SEI competencies among students exposed to internationalization experiences, particularly in specific dimensions of these competencies. Internationalization of the Curriculum (IoC) was found to have positive effects as a catalyst for SEI competency development, with results comparable to those of international mobility experiences (IA) when contrasted with internationalization at home (IaH). These findings underscore the potential of both types of internationalization to enhance the quality, equity, and inclusiveness of Higher Education, contributing to the holistic education of students.